Dedication to the Imperial Family’s Genius (Genius Domus Augusta) from Oneum (Archaeologia Adriatica, 2022)
This paper provides a picture of imperial worship in Roman Oneum, wherein the primary focus is on an altar dedicated to Divus Augustus, the goddess Roma and the imperial family’s Genius (Genius domus Augusta). This is a rather intriguing cult artefact, not only because of its multiple dedications, but also due to the fact that it was installed by an auxiliary military unit, Cohors I Gallica Voluntariorum, which is also the first time this cohort was mentioned in the province of Dalmatia.
Keywords: Salona; Oneum; Tiberius; Drusus; Cohors I Gallica Voluntariorum; provincial imperial cult; Genius domus Augusta